Naẓariyyat Ibn Khaldūn fī Iktisāb al-Lughah - Alif Cahya Setiyadi (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
Language is a uniquely human phenomenon that distinguishes human beings from all other creatures. Humans are born with the biological organs necessary for speech as well as cognitive abilities that enable them to acquire language. Various theories have been proposed to explain the process of language acquisition, each emphasizing a different primary factor underlying this process. Among the most influential are behaviorist, cognitive, and innatist (nativist) theories. In addition to these well-known perspectives, Ibn Khaldun presented important ideas on first language acquisition in his Muqaddimah. Although his views have received comparatively little attention, Ibn Khaldun is widely recognized as a distinguished Muslim thinker, the founder of sociology, a political scholar, a philosopher of history, and an eminent linguist. This article examines Ibn Khaldun’s theory of first language acquisition, highlighting the close relationship between language and society. According to Ibn Khaldun, language exists only within a social community because it functions as the primary means of communication and interaction among people. His theory emphasizes that language acquisition is fundamentally rooted in social life and human interaction.